Racial Transition - Yuvraj Joshi (Washington University Law Review, 2021)
The United States is a nation in transition, struggling to surmount its racist past. This transitional imperative underpins American race jurisprudence, yet the transitional bases of decisions are rarely acknowledged and sometimes even denied. This Article uncovers two main ways that the Supreme Court has sought “racial transition.” While Civil Rights era decisions focused on “reckoning” with the legacies of racism, more recent decisions have prioritized “distancing” the United States of today from its antebellum and Jim Crow histories. With this shift, civil rights measures that were once deemed necessary and urgent have been declared inappropriate and outdated. By rereading opinions concerning school desegregation, voting rights, affirmative action, and disparate impact in terms of reckoning and distancing, this Article provides key insights into racial equality law’s history as well as a glimpse into its likely future under the Roberts Court. Because both reckoning and distancing approaches claim to advance transition, this Article evaluates these approaches from the perspective of transitional justice, a field that helps societies to overcome histories of oppression. This analysis highlights how the Supreme Court’s inadequate treatment of transitional justice values (accountability, redress, non-repetition, and reconciliation) has inhibited America’s transition from white supremacy. Transitional justice theory further offers a novel account of judicial disagreements and independent criteria for deciding which claims about transition should have purchase. As protestors demand a reckoning with America’s legacies of racism, the Roberts Court appears poised to leave the past behind. A distancing jurisprudence limits not just what the Court sees as constitutionally required, but what it sees as constitutionally permissible in the pursuit of transition. This Article considers how advocates can seek to reorient race jurisprudence toward greater racial reckoning, while simultaneously pursuing reckoning through other means.
Keywords: Racial transition; Racial justice; Transitional justice; Roberts Court